Protestant Bible Scholarship: Antisemitism, Philosemitism and Anti-Judaism - Bakker, Arjen F.; Bloch, René; Fisch, Yael; Fredriksen, Paula; Najman, Hindy (Brill, 2022)
Historical criticism of the Bible emerged in the context of protestant theology and is confronted in every aspect of its study with otherness: the Jewish people and their writings. However, despite some important exceptions, there has been little sustained reflection on the ways in which scholarship has engaged, and continues to engage, its most significant Other. This volume offers reflections on anti-Semitism, philo-Semitism and anti-Judaism in biblical scholarship from the 19th century to the present. The essays in this volume reflect on the past and prepare a pathway for future scholarship that is mindful of its susceptibility to violence and hatred.